EXPLORING HOTEL EMPLOYEE WELLBEING : POSITIVE IMPACTS OF CAREER DEVELOPMENT AND WORK COMPENSATION - Adzandri, Faraz; Saputra, Andri Satrio; Mendrofa, Agung Braja; Ferdian, Feri (Family Welfare Education, 2023)
Hospitality is a rapidly growing sector in various countries around the world. In this industry, hotel employees play a very important role in providing quality service to guests. However, the hospitality industry is often faced with challenges in retaining employees, mainly due to job satisfaction issues. Employees who are dissatisfied with their jobs tend to leave the company and seek employment elsewhere. To overcome this problem, it is important to understand the factors that influence the hotel employee's wellbeing. The purpose of this study was to examine the influence of employee career development and work compensation on hotel employee wellbeing. The study used a quantitative with a causal associative approach. The data was obtained by distributing questionnaires to the 4 star hotel employees at Batam City, so that as many as 40 respondents. The data analysis technique used the Partial Least Square Structural Equation Modeling. Most of the respondents are aged from 26 to 30 years . with 67.5% of the respondents. The study’s findings indicate that career development is not particularly significant in relation to hotel employee wellbeing. However, this has a direct impact on raising motivation, work ethic, and organizational commitment, which in turn raises employee morale. Meanwhile, compensation for work has a significant positive impact on hotel staff members' ethical standards. These findings suggest that Hotels may achieve a greater level of operational excellence and keep up their competitiveness in the hospitality sector by focusing on the well-being of employees.